Core‐SOL simulations of high‐power JET‐ILW pulses fuelled with gas and/or with pellets. Issue 5 (23rd May 2022) - Telesca, Giuseppe; Chomiczewska, Agata; Frigione, Domenico; Garzotti, Luca; Huber, Alexander; Ivanova‐Stanik, Irena; Kowalska‐Strzeciwilk, Ewa; Lomas, Peter; Perez von Thun, Christian; Rimini, Fernanda; Van Eester, Dirk; Zagórski, Roman; et al.
Abstract: Experimental analysis of two couples of pulses in the range of input power of 26–32 MW, shows that addition of pellet throughput to high gas dosing pulses does not modify the plasma energy, but leads to better conditions as far as the tungsten concentration and core radiation are concerned. Significantly decreasing the gas dosing with addition of high pellet throughput causes the increase of plasma energy, but the W concentration increases from 5.2 × 10 −5 to 6.9 × 10 −5 and the core radiation from 7.5 to 11 MW. From the numerical results of the self‐consistent core‐SOL COREDIV code two mechanisms appear to be responsible for the observed different W concentrations: the core residence time of W, which is related to the energy and particle confinement time, and the divertor impurity screening efficiency, dependent on the electron density and on the perpendicular transport coefficient in the SOL.